PERAN PARENT CHILD RELATIONSHIP PADA PEMBENTUKAN ORIENTASI SEKSUAL LESBIAN - Lika Purnama Ning Wulan; Diana Rahmasari (Universitas Negeri Surabaya, 2021)
Abstrak Perkembangan jaman yang semakin modern dan cepat seperti sekarang ini tentu saja memengaruhi gaya hidup masyarakat dalam kebutuhan primer salah satunya pada fashion. Hal ini memberi pengaruh yang besar kepada konsumen terutama mahasiswa di kota besar seperti Surabaya yang memiliki persepsi terkait baju dengan gaya kekinian, berasal dari merk terkenal, dan memiliki harga yang murah seperti thrift clothes import. Persepsi seperti ini memiliki keterkaitan terhadap keputusan pembelian produk. Penelitian ini bertujuan untuk mengetahui hubungan antara persepsi konsumen terhadap keputusan pembelian pada mahasiswa Psikologi Universitas Negeri Surabaya. Penelitian ini merupakan penelitian kuantitatif dengan subjek 55 orang mahasiswa Psikologi di Universitas Negeri Surabaya. Analisis korelasi data dalam penelitian ini menggunakan pearson product moment. Hasil analisis korelasi data sebesar 0,753 (r = 0,753) dengan taraf signifikansi linier 0,000 (p<0,05) menunjukkan adanya hubungan positif dan linier antara persepsi konsumen dengan keputusan pembelian. Kata Kunci: persepsi konsumen, keputusan pembelian, thrift clothes import Abstract Lesbian sexual orientation is defined as a woman who has feelings of love emotionally, spiritually, and physically to other women. It was found that one of the factors that influence why someone becomes a lesbian is a poor relationship between parents and children. The purpose of this study was to determine the role of parent-child relationships in the formation of lesbian sexual orientation. The method used in this research is a qualitative approach with a case study method. The research subjects were three women in the age range of 20-22 who had a lesbian sexual orientation, had gone through the process of coming out, and since childhood were cared for by their parents themselves. Data were collected using semi-structured interviews and analyzed using thematic analysis. This study found three main themes, namely the condition of parenting which consists of three sub-themes (father's role, mother's role, attachment to parents), then the second theme of lesbian identity formation which consists of two sub-themes (early awareness of lesbians, and social learning ) and the last theme is coming out which is divided into two sub-themes (coming out process, and parental response). In particular, this study found that permissive and authoritarian parenting, and insecure attachment types contributed to the formation of lesbian sexual orientation. Key words: parent-child relationship, sexual orientation, lesbian